Sekuen Internal Transcribed Spacer (ITS) DNA ribosomal Oncobasidium theobromae dan jamur sekerabat pembanding Internal Transcribed Spacer (ITS) sequences of ribosomal DNA Oncobasidium theobromae and other related fungi as comparison - Agustin Sri MULYATNI; Achmadi PRIYATMOJO; Agus PURWANTARA (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2011)
AbstractThe objective of this research was to sequence ITSregion from ribosomal DNA of Oncobasidium theobromae,and to compare the sequences to the isolates from Vietnamand Malaysia, and also to identify other related fungi speciesbased on the homology of the ITS region. O. theobromae wasisolated from three cocoa plantations in Indonesia that wereJember, Kendari, and Makasar. DNA was isolated from thefungal mycelia, and then amplified using ITS-4 and ITS-5primers, resulted in DNA fragments of 600 bp and 700 bpfor the isolate from Jember, 600 bp for the isolate fromKendari, and 700 bp for the isolate from Makasar. All of thefragments were successfully sequenced, except for 600 bpfragment of the isolate from Jember. The homology analysisusing BLAST was confirmed that ITS sequencesO. theobromae from Jember was homolog with Rhizoctoniasp. and Ceratobasidium sp., whereas isolate from Kendariwas homolog with Botryosphaeria sp. and isolate fromMakasar was homolog with Mycorrhizal basidiomycetes. Thesequences were then compared to the sequences ofO. theobromae from Vietnam and Malaysia. Phylogeneticanalyses using Clustal W program indicated thatO. theobrome from Indonesia which is represented byisolates from Jember showed higher degree of similarity toisolates from Vietnam. On the contrary, isolates fromIndonesia showed lower degree of similarity to isolates fromMalaysia.AbstrakPenelitian ini bertujuan untuk mengetahui sekuen daerahITS dari DNA ribosomal jamur Oncobasidium theobromae,dan membandingkannya dengan sekuen jamur O. theobromaeyang berasal dari Malaysia dan Vietnam, serta untukmengidentifikasi spesies lain yang merupakan kerabat dekatO. theobromae dengan berdasarkan kemiripan sekuenITSnya. Isolat jamur O. theobromae diisolasi dari tiga lokasiperkebunan kakao di Indonesia yaitu Jember, Kendari danMakasar. DNA diisolasi dari miselium jamur. Amplifikasidaerah ITS menggunakan primer ITS-4 dan ITS-5menghasilkan fragmen 600 bp dan 700 bp untuk isolatJember, 600 bp untuk isolat Kendari dan 700 bp untuk isolatMakasar. Semua fragmen berhasil disekuensing kecualifragmen Jember 600 bp. Analisis homologi menggunakanBLAST menunjukkan fragmen isolat Jember 700 bpmemiliki homologi tertinggi dengan Rhizoctonia sp. danCeratobasidium sp., isolat Kendari 600 bp homolog denganBotryosphaeria sp., dan isolat Makasar homolog denganMycorrhizal basidiomycetes. Hasil sekuen tersebut kemudiandibandingkan dengan sekuen daerah ITS O.theobromae dariMalaysia dan Vietnam untuk mengetahui hubungankekerabatannya. Analisis kekerabatan menggunakan programClustal W menunjukkan O. theobromae dari Indonesia yangdiwakili oleh isolat Jember berkerabat dekat dengan isolatVietnam, akan tetapi tidak dengan isolat Malaysia.